ПРАВОСЛАВНАЯ МОЛДОВА В ПРАВОВОЙ ШКАЛЕ ЕВРОСОЮЗА: АСПЕКТЫ РЕЛИГИОЗНОЙ ТОЛЕРАНТНОСТИ - Роговая, Галина (SUPREMANCE OF LAW, 2018)
This article explores the problem of observing the rights of Orthodox believers, who in the Republic of Moldova have a majority. Attention is drawn to the religious factor as a factor of inhibition of the process of Moldova’s integration into the EU. At the same time, concern is expressed about the observance of the rights of Orthodox citizens and the preservation of their spiritual comfort in case of Moldova joining the European Union. After all, the religious tolerance of the Orthodox differs from the religious tolerance of Catholics and Protestants, of whom the majority in the EU.
Keywords: European integration; inertial factors of the integration process; orthodox believers; catholics; protestants; Holy Bible; religious tolerance; intolerance